2001
DOI: 10.1099/00221287-147-11-2961
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate synthase of Corynebacterium glutamicum is not essential for glutamate synthesis and is regulated by the nitrogen status

Abstract: The Corynebacterium glutamicum gltB and gltD genes, encoding the large (α) and small (β) subunit of glutamate synthase (GOGAT), were investigated in this study. Using RT-PCR, a common transcript of gltB and gltD was shown. Reporter gene assays and Northern hybridization experiments revealed that transcription of this operon depends on nitrogen starvation. The expression of gltBD is under control of the global repressor protein AmtR as demonstrated by gel shift experiments and analysis of gltB transcription in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 33 publications
(23 reference statements)
1
53
0
Order By: Relevance
“…Strain MJ6-18 carries a genomic amtR deletion [13], which leads to the lack of the master regulator of nitrogen control, AmtR. As a consequence, genes encoding the enzymes of the glutamine synthetase-glutamate synthase pathway (GS/GOGAT) [3,24] and ammonium carriers AmtA and AmtB [23,31] are constitutively expressed. Double deletion strain TMDgdhDglnA is lacking the ammonium assimilation enzymes glutamate dehydrogenase and glutamine synthetase (GS I).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Strain MJ6-18 carries a genomic amtR deletion [13], which leads to the lack of the master regulator of nitrogen control, AmtR. As a consequence, genes encoding the enzymes of the glutamine synthetase-glutamate synthase pathway (GS/GOGAT) [3,24] and ammonium carriers AmtA and AmtB [23,31] are constitutively expressed. Double deletion strain TMDgdhDglnA is lacking the ammonium assimilation enzymes glutamate dehydrogenase and glutamine synthetase (GS I).…”
Section: Resultsmentioning
confidence: 99%
“…As in C. glutamicum, this is caused by osmotic or ionic stress rather than by ammonium toxicity, as shown by the addition of sodium sulfate to cells, which led to even severe effects (Table 2). It might be speculated that the less drastic effect of ammonium compared to sodium is the result of a faster equilibration due to diffusion of NH 3 and resulting smaller osmotic gradients between medium and cytoplasm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that extracellular GS may manipulate phagosome pH modulation and consequently prevent phagosome-lysosome fusion (27,26). Furthermore, extracellular GS1 has been implicated in the synthesis of poly-L-glutamine-glutamate, a cell wall constituent of pathogenic mycobacteria (27)(28)(29), which may play a role in cell wall integrity. M tuberculosis GS1 lacks a leader peptide sequence and is considered to be an intracellular protein in most other bacteria, thus its abundance in the extracellular environment of M. tuberculosis and other pathogenic mycobacteria (26) has become a focus of study.…”
Section: Nitrogen Assimilation: the Gs/gogat Systemmentioning
confidence: 99%